Identifikasi dan Kuantifikasi Limbah Bahan Berbahaya Dan Beracun (LB3) Pada Industri X Di Kota Bandung - Eka Wardhani; Aldi Prasetya Triatmaja (Jurnal Serambi Engineering, 2021)
The rapid development and development of the electronics industry in Bandung has both positive and negative impacts. The negative impact given is in the form of hazardous and toxic waste (HTW) which will have negative consequences if not managed properly. Evaluation of the management of HTW is an important thing to do to ensure that the management is in accordance with regulations. The purpose of this study is to identify and quantify the types and amounts of HTW in  industry X Bandung City. This company is engaged in electronics with a domestic market share. Descriptive observational research with the objects in the form of activities of the production process, source, reduction process, packaging, storage, labeling and transportation of HTW. Data collection time was carried out in July 2019-June 2020. Based on the results of the study, it was found that used IPA (isophthalic acid liquid) was the most HTW produced followed by contaminated materials such as broken cells/modules, used coolants, used personal protective equipment, rags and pieces of PCB. The total HTW produced is 1,176 tons/year, where the amount of used IPA (isophthalic acid liquid)  0.414 tons /year.